Possible factors responsible for increased risk of tendon injuries during strength training in adult patients: systematic review - Zbigniew Wroński; Burim Gjinovci; Mario Klasic (Physiotherapy Review)
Exercise is a fundamental aspect of physiotherapy, with an increasing number of studies focusing on tendon problems. This review aims to identify situations where physiotherapists should exercise caution and precision when prescribing resistance exercises. Aims: This study aimed to analyze factors responsible for an increased risk of tendon injuries during resistance training in adult patients. Material and methods: A search was conducted in June and July 2023 in PubMed/Medline, EMBASE, Science Direct, PEDro, and Cochrane databases. Clinical trials, meta-analyses, randomized controlled trials, reviews, and systematic reviews published within the last ten years were included if they considered strength and resistance training as risk factors for tendon injuries. Studies on in vitro tissues, post-surgery patients, or lacking training procedure descriptions were excluded. Results: During the search conducted in June and July 2023, 538 articles were analyzed. 6 articles meet criteria, and 1 other were found valuable even thou were not meeting criteria fully. Conclusions: There is a potential greater risk for tendon injuries in obese patients, particularly in the upper extremities; in female patients; when antibiotics such as fluoroquinolones, ofloxacin, and norfloxacin are administered with corticosteroids; and in individuals with noticeable strength deficits.